Pembentukkan Kampung Iklim Di RW 13 Kelurahan Umban Sari Kota Pekanbaru - Trio Saputra; Wasiah Sufi; E Eka (LPPM STIKOM Tunas Bangsa, 2022)
Partners who are the target of community service activities are RW 13 Umban Sari Pekanbaru City. Based on the results of observations and interviews, there are 3 main problems faced by partners including (1) there are not many people in RW 13 who know about the climate village program (2) there is no data and information on adaptation and mitigation of climate village programs (3) RW 13 Umban sari has not been registered on the SRN website. Based on the above problems, solutions are offered (1) socialization of the climate village program (2) assistance in inventorying potential data for the climate village program (3) training in filling out data on the SRN website. This program activity uses an educative method with training and mentoring. The results of service activities (1) community knowledge about the climate village program in RW 13 can be understood after socialization. (2) the data on potential climate village programs in RW 13 Umban Sari Rumabai. (4) the registration of RW 13 on the SRN website as a form of participation in the climate village program.